A characterization of the natural isomorphism of bifunctors - Mejía Alemán, Carlos (2023)
We are going to characterize the natural isomorphism between the bifunctors of the examples 2.13 and 2.14, for that it is enough to show that η and ζ of the lemma 3.1 are natural isomorphisms.